Hubungan Verbal Bullying Dengan Kesepian Pada Remaja Korban Bullying di Pondok Putri Hafshawaty Pesantren Zainul Hasan Genggong Probolinggo - Riska Wati; Iin Aini Isnawati; Alwin Widhiyanto (Pusat riset dan Inovasi Nasional, 2023)
Verbal bullying is a form of intimidation through words such as threatening, mocking, calling names with inappropriate nicknames, which are intended to humiliate or destroy the victim. One of the effects of bullying is low self-esteem, anxiety and even more severe loneliness, which makes individuals do not want to interact socially and isolate themselves. This study aims to determine whether there is a relationship between verbal bullying and loneliness in adolescent victims of bullying.This research method used correlational analytic with cross sectional approach. With a total sample of 46 respondents, the sampling approach employed on verbal bullying and loneliness respondents is total sampling. The results of this study found that there were victims of bullying with high verbal bullying criteria as many as 24 respondents (52.2%) and experiencing severe loneliness as many as 25 respondents (54.3%) with value 0.001 <0.05. It can be concluded that there is a relationship between verbal bullying and loneliness, namely individuals who experience verbal bullying result in significant loneliness because the individual does not want to socialize properly and feels that he is not useful to others.The management's approach to the students while providing HE about understanding bullying and other anticipations that can be done by the administrators is to establish a